2010
DOI: 10.1038/npp.2009.222
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of the Periaqueductal Gray by Mild Anxiogenic Stress at Different Stages of the Estrous Cycle in Female Rats

Abstract: The effect of acute exposure to mild anxiogenic stress on cutaneous nociceptive threshold was investigated in female Wistar rats at different stages of the estrous cycle. Baseline tail flick latencies did not change significantly during the cycle. However after brief exposure to vibration stress (4 Hz for 5 min), rats in late diestrus, but not at other cycle stages, developed a hyperalgesia (decrease in tail flick latency). Animals in late diestrus revealed a more than fivefold increase in the density of Fos-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…The fact that a panicogenic challenge with CO 2 [132, 196] or intravenous sodium lactate [113, 318] causes premenstrual dysphoric disorder (PMDD) patients to display panic attacks at about the same rate as in panic disorder patients further indicates a common underlying psychobiology [368]. Rodent as well as human research [190, 260, 274, 333] now proposes a three-factor interaction between (a) the rate at which progesterone and its anxiolytic metabolite allopregnanolone drop during the late luteal phase (humans) or during late diestrus (comparable phase in rodents) [221, 222, 314], (b) γ-aminobutyric acid (GABA) A receptor sensitivity, kinetics, and subunit assembly in stress-coping circuitries including the amygdala and the periaqueductal gray (PAG) [143, 147], and (c) external stressors [94, 95, 340] as a model of sex-dependent predisposition for panic disorder [268]. …”
Section: Human Gender Differences In Anxiety and Emotional Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that a panicogenic challenge with CO 2 [132, 196] or intravenous sodium lactate [113, 318] causes premenstrual dysphoric disorder (PMDD) patients to display panic attacks at about the same rate as in panic disorder patients further indicates a common underlying psychobiology [368]. Rodent as well as human research [190, 260, 274, 333] now proposes a three-factor interaction between (a) the rate at which progesterone and its anxiolytic metabolite allopregnanolone drop during the late luteal phase (humans) or during late diestrus (comparable phase in rodents) [221, 222, 314], (b) γ-aminobutyric acid (GABA) A receptor sensitivity, kinetics, and subunit assembly in stress-coping circuitries including the amygdala and the periaqueductal gray (PAG) [143, 147], and (c) external stressors [94, 95, 340] as a model of sex-dependent predisposition for panic disorder [268]. …”
Section: Human Gender Differences In Anxiety and Emotional Disordersmentioning
confidence: 99%
“…During late diestrus (late luteal phase in humans), concentrations of progesterone and its anxiolytic metabolite allopregnanolone [400, 401] rapidly drop, and this decrease in allopregnanolone alters the subunit composition of the GABA A receptor, meaning a shift towards decreased expression of the α1 subunit and increased expression of the α4, β1, and δ subunits [143]. This reduces the ongoing inhibitory output of the GABA neurons within the PAG [222] and is correlated with increased anxiety-like behaviors in diestrus rats, but not proestrus, metaestrus, or estrus rats [93, 94]. Decreased inhibitory output from GABAergic PAG neurons during diestrus is likely to disinhibit the DPAG and thus reduce the suppression of panic-like responses.…”
Section: Potential Mechanisms For Sex Differences In Stress-related Amentioning
confidence: 99%
“…Alternatively, it may not be the absolute level of E2 that is important, but changes in concentration (i.e., fluctuating levels during the estrous or menstrual cycle). Estrogen or progesterone withdrawal may be more significant in modulating nociceptive sensitivity than maintaining a high level of either hormone (Devall and Lovick, 2010; Heitkemper and Chang, 2009; Ji et al, 2003; Martin et al, 2007; Martin, 2008; Puri et al, 2011; Robbins et al, 2010). Finally, the site where hormones produce their effect, peripheral tissue or the central nervous system (CNS), likely influences any conclusions.…”
Section: Animal Studies Supporting a Sex Difference And Hormonal Mmentioning
confidence: 99%
“…On the contrary, decreased withdrawal thresholds were observed in males, but not in females. It is reported that brief exposure to vibration-stress (4 Hz for 5 min) causes hyperalgesia in rats, as evidenced by a decrease in tail flick latency [37]. This kind vibration may be regarded as a mild, non-noxious type of stressor.…”
Section: Weak (15g) Gravity Stressmentioning
confidence: 99%